Impact of Corporate Entrepreneurship and Organizational Culture on Business Performance: The Role of Supply Chain Management - Hong Van Pham; Huynh Xuan Nguyen; Dinh Tran Ngoc Huy (International Journal of Supply Chain Management, 2020)
With the expanding multifaceted nature and vulnerability of worldwide inventory chains, interruption occasions are as often as possible happening in production network. Commercial condition is separated into two sorts including inner and outer business conditions. In the examination, our inward business condition is organization culture and inside business condition is supply chain performance (SCP). Therefore, the purpose of this study is to quantify the impact of organizational culture (OC), corporate entrepreneurship (CE) and its components on business performance (BP) through SCP in the non-financial sector of Thailand. Research sample comprises of 120 non-financial firms operating in Thailand. The study finds that SCP fully mediates the relationship between work reinforcement BP and time availability and BP. Whereas, SCP is found to have partial mediation in the relationship between CE BP, OC BP, management support BP, organization boundaries BP and reward reinforcement and BP. Findings of study are important for mangers in understanding and implementation of better OC which leads to CE and will ultimately enhance BP.